Identifying the spatial differentiation factors of traditional villages in China - Wanxu Chen; Zhen Yang; Liyan Yang; Jianhua Wu; Jiaojiao Bian; Jie Zeng; Zhiling Liu (Heritage Science, 2023)
Abstract China's agricultural civilization had left numerous traditional villages (TVs) containing rich historical information and cultural landscape. Exploration the spatial agglomeration characteristics of TVs and their influencing factors is essential for the sustainable development, utilization, and protection of TVs in China. However, previous studies lacked a comprehensive analysis of the spatial distribution of TVs and their driving factors, especially at the national scale. To fill this gap, this study analyzed the spatial agglomeration characteristics and influencing factors of five batches of TVs in China during 2012–2019. The results show that TVs in China were mainly located east of the Hu Line, that is, in the southern and eastern regions of China. The spatial distribution of TVs had significant clustering characteristics, and the gravity center was mainly distributed in central China, and the compactness of the spatial distribution of TVs increased from the first to the fifth batches. The TVs were mainly located at low elevations, northern slope aspect, warm and humid areas. Ferralisol and cultivated vegetation were the main soil and vegetation types in most TVs. TVs tended to be more numerous in the vicinity of low economic development levels, low population density, and rivers. In addition, TVs had a significant correlation with intangible cultural heritage. The results of this study could provide scientific guidance for heritage protection and sustainable development of TVs.